Roost tree characteristics of Egyptian vulture (Neophron percnopterus) in the Chitwan-Annapurna Landscape, Nepal - Pariyar, Ashish; Bhusal, Krishna Prasad; Byrd, George Vernon; Bhusal, Dinesh; Bhattarai, Suman (FORESTRY: Journal of Institute of Forestry, Nepal, 2025)
Conservation of the endangered Egyptian vulture (Neophron percnopterus) in Nepal would benefit from more information on its specific habitat needs. This study investigated the characteristics of roost trees, including the number of Egyptian Vultures present, from December 2024 to March 2025, at 13 sites across the Chitwan–Annapurna Landscape (CHAL), where the species was known to occur. A total of 152 trees of 13 different species were identified as the roost trees of Egyptian vultures based on the presence of the birds or their droppings and feathers underneath. Bombax ceiba was the most common species used. Egyptian vulture roost trees were relatively large (mean diameter at breast height: 57.8 ± 17.22 cm, height: 17.9 ± 3.93 m and crown width: 10.90 ± 3.05 m), compared to nearby unused control trees (34.81 ± 7.31 cm, 11.71 ± 3.10 m, 5.73 ± 1.64 m). Most roost trees were located on the northeast (49%) and northwest (21%) aspects, with an average slope of 14.4°, although other slope and aspect features were available in all study sites. Distance to food sources and water bodies were significant predictors of the number of Egyptian vultures using the roost trees. When summed among sites, the peak count of Egyptian vultures totalled 566, with the peak number at different roost sites ranging from < 10 (7 of the sites) to 378 (Dovilla) individuals. Crown width, height of tree, distance to water bodies, and slope were significant predictors of the number of vultures at roost sites. These findings provide baseline information for planning conservation efforts to save the roost trees of Egyptian vulture and minimize threats to them.